Distance Education among Italian Teachers: Differences and Experiences - Menabò, Laura; Skrzypiec, Grace; Sansavini, Alessandra; Brighi, Antonella; Guarini, Annalisa (Education and information technologies, 2022)
The successful integration of technology in teaching is a key component of education. Although prior research highlighted factors fostering the use of technology by teachers, few studies focused on whether these factors vary among teachers of different grade levels and subjects. Moreover, no studies have investigated personal experiences related to distance education among a large sample of teachers. To address these gaps, the present mixed-method study sought to examine whether factors promoting distance education varied among Italian teachers of different grade levels and subjects. A further aim was to explore experiences of teachers using distance education. The sample involved 357 Italian teachers and preservice teachers who completed an online questionnaire during the COVID-19 pandemic that also contained open-ended questions. Findings indicated that teaching self-efficacy was greater in pre-service and primary teachers, while facilitating conditions were greater in humanities and science secondary teachers. The perceived ease of use of technology and technology for pedagogy skills were more pronounced among science secondary teachers. Advanced technology skills were lower in humanities secondary teachers while the behavioural intention to use technology was greatest among pre-service teachers. Four themes emerged from the qualitative study of teachers’ insights. These included positive and negative aspects of using technology, the relationship with students, the versatility of distance education, and the quality of lessons. This study underscores the need to address training based on different teachers’ grade levels and subjects, and to focus on the emerging themes to better integrate the use of technology in schools.